Status of Private Plantation and their Management in Siraha distict of Nepal: A case study - Singh, Satish Kumar; Poudyal, Arun Sharma; Shah, Jit Narayan; Kumar, Vikas; Das, Subhash Chandra (Indian Forester, 2022)
The research work was conducted to find out the status of private forests with the major species planted and managed in the Terai. Additionally, the present status of private forests and the scenarios of selling procedure, and the silviculture practices that are applied, were studied and form a basis on which further research could be carried out. The research is based on a descriptive and field survey. The serious issue recognized that upset the private forest improvement was the absence of land accessibility, lack of seedling of the desired tree species, absence of specialized information, absence of fitting business sector and market cost, and inappropriate timber utilization. The discoveries additionally incorporate that an uncommonly moderate pace of private forest registration, long and multi-stage forms for getting, collecting and transportation licenses and authority bans on significant commercial species, among others, are seen as the variables that most ruin the private forest proprietors and tree producers interest and their advantages and obligations concerning the association and utilization of their private forest assets. It is concluded that a disentangled allowing process would elevate and assist private forestry.